Once‐weekly prophylaxis with glycoPEGylated recombinant factor VIII (N8‐GP) in severe haemophilia A: Safety and efficacy results from pathfinder 2 (randomized phase III trial). Issue 3 (28th February 2019) - Curry, Nicola; Albayrak, Canan; Escobar, Miguel; Andre Holme, Pål; Kearney, Susan; Klamroth, Robert; Misgav, Mudi; Négrier, Claude; Wheeler, Allison; Santagostino, Elena; Shima, Midori; Landorph, Andrea; et al.
Abstract : Introduction: Turoctocog alfa pegol (N8‐GP) is a site‐specific, 40 kDa glycoPEGylated recombinant factor VIII (FVIII) product with an extended half‐life. The comprehensive main phase of the pivotal pathfinder 2 trial showed N8‐GP dosed every 4 days (Q4D) provided favourable safety and efficacy for preventing bleeds in 175 patients with haemophilia A. Aim and methods: We investigated the safety and efficacy of N8‐GP prophylaxis when administered weekly (Q7D) for 24 weeks to patients with low bleeding rates in the pathfinder 2 extension trial. Patients (≥12 years) with ≤2 bleeds during the preceding 6 months of the pathfinder 2 main phase were eligible for randomization to receive N8‐GP 50 IU/kg Q4D or 75 IU/kg Q7D. Safety and efficacy endpoints were incidence of FVIII inhibitors and annualized bleeding rate (ABR), respectively. Results: Fifty‐five of 143 (38.5%) patients on prophylaxis who continued into the extension phase were randomized to receive 50 IU/kg Q4D (n = 17) or 75 IU/kg Q7D (n = 38). Nine patients in the Q7D cohort reverted to 50 IU/kg Q4D. No inhibitors were detected. In both cohorts, >50% of patients experienced no bleeds. Median ABR for overall, joint, spontaneous, traumatic and muscle was 0.00 for both cohorts. Overall estimated success rate for treating bleeding episodes was 87.5%; 94.7% of bleeds were controlled with ≤2 injections. Conclusions: Weekly N8‐GP was well tolerated and efficacious and may benefit selected "low bleeder" patients with haemophilia A.